A Multiple Compression Approach using Attribute-based Signatures - Costa, Marios; Costa, Constantinos; Chrysanthis, Panos; Herodotou, Herodotos; Stavrakis, Efstathios; Nikolaou, Nikolas (My University, 2025)
With the increasing volume of data collected for advanced analytical and AI applications, data storage remains a significant challenge. Despite advancements in storage technologies, the cost of maintaining vast datasets continues to grow. Compression techniques have been widely used to address this issue, but existing systems primarily rely on a single, typically lossless method, which limits adaptability to varying data characteristics.